EFEKTITIFAS PROGRAM PEMBINAAN KEDISIPLINAN PROSES BELAJAR MENGAJAR DALAM PENINGKATAN ETOS KERJA MANDIRI GURU DI SMPN 3 BULAGI SELATAN: SMP NEGERI 3 BULAGI SELATAN, KECAMATAN BULAGI SELATAN KABUPATEN BANGGAI KEPULAUAN - YONIS HAMISDIN SOPUK (Mitra Pendidikan, 2022)
The purpose of this study was to determine whether or not there is a relationship between teaching discipline in the classroom and improving the quality of self-competence for teachers at SMPN 3 Bulagi Selatan, Banggai Islands, Odd Semesters for the 2021/2022 Academic Year. The type of research used in this study is a type of qualitative research. This qualitative research is descriptive in the form of speech and writing that can be observed from the subject itself (Arif Furchan. 1992). While the approach used in this research is a case study. Case study research is technically a research conducted intensively, in detail, and in depth on a particular symptom or phenomenon in an organization, institution (Suharsimi Arikunto. 2002). This research was carried out at SMPN 3 Bulagi Selatan, Banggai Islands Regency for 3 months, from September to November 2021. The subjects in this study were teachers at SMPN 3 Bulagi Selatan, Banggai Islands Regency, totaling 18 teachers. Based on the results of the discussion that has been described, it can be concluded. Based on data analysis, from this research it can be concluded that the implementation of inspections and official visits by educational supervision is very helpful for teachers at SMPN 3 Bulagi Selatan Banggai Islands Odd Semester Academic Year 2021/2022 Sulawesi Province In the midst of the disciplined attitude of the teacher, the discipline of the teacher will greatly affect the results of teaching work in the classroom.